2021
DOI: 10.1007/s00264-021-04992-9
|View full text |Cite
|
Sign up to set email alerts
|

Three dimension printing talar prostheses for total replacement in talar necrosis and collapse

Abstract: Background Reconstructing bone structures and stabilizing adjacent joints are clinical challenges in treating talar necrosis and collapse (TNC). 3D printing technology has been demonstrated to improve the accuracy of talar replacement. This study aimed to evaluate anatomical talar replacement and the clinical results. Methods Nine patients with TNC were enrolled between 2016 and 2020. The prosthetic shape and size were designed by CT post-processing and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…For the prosthesis-bone interface needing screw xation, a special coating is often used to achieve the biomechanical effect of bone ingrowth. Professor Tang Kanglai's team conducted a series of studies on this topic and has made clinical progress [27][28]. The operation is similar to fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For the prosthesis-bone interface needing screw xation, a special coating is often used to achieve the biomechanical effect of bone ingrowth. Professor Tang Kanglai's team conducted a series of studies on this topic and has made clinical progress [27][28]. The operation is similar to fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For prosthesis-bone interfaces needing screw xation, a special coating is often used to achieve the biomechanical effect of bone ingrowth. Professor Tang Kanglai conducted a series of studies on this topic and made clinical progress [27,28]. The operation is similar to fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…( Angthong, 2014 ; Taniguchi and Tanaka, 2019 ) Due to the unique anatomic form of the talus, the vital element for a successful prosthetic TTR is the congruency of the custom-made implant with the adjacent joints. ( Mu et al, 2021 ) Despite the rapid development of TTR prostheses however, full reconstruction of the anatomic features of a native talus—which would optimally stabilize and maintain normal ankle function—remains a challenge. ( Ando et al, 2016 ) Three-dimensional (3D) printing technology integrated with computed tomography (CT) imaging and computer-aided design has now been widely used in surgical planning and custom-made implant design, to achieve anatomic accuracy in talar prosthetic design and production.…”
Section: Introductionmentioning
confidence: 99%
“…( Ando et al, 2016 ) Three-dimensional (3D) printing technology integrated with computed tomography (CT) imaging and computer-aided design has now been widely used in surgical planning and custom-made implant design, to achieve anatomic accuracy in talar prosthetic design and production. ( Akoh et al, 2020 ; Mu et al, 2021 ) 3D printing has shown tremendous potential for the design and production of refined structures with irregular shapes and free surfaces such as the talar body. Thus, the utilization of 3D printing technology in conjunction with TTR may be a promising way for surgeons to provide more personalized, anatomically accurate, and above all more durable surgical solutions with better long-term prognoses.…”
Section: Introductionmentioning
confidence: 99%